Analysis of parameter influence law of waveguide Bragg grating. (February 2022) - Zheng, Yu; Yue, Jiangtao; Zhang, Pan; Duan, Ji'an
Highlights: The periods of the Bragg gratings are not directly given and are calculated automatically by the software. The sensitivity analysis does not take into account the part where the parameters have little effect on the performance. In the sensitivity analysis, some mutation values were abandoned. Abstract: External cavity narrow linewidth laser has a wide range of applications in optical communication, optical sensing and other fields, and its performance largely depends on the external cavity waveguide grating. In this paper, the factors affecting the performance of the grating are analyzed in detail by using the Morris screening method, and the influence law and degree of each factor on the performance are given. Based on the analysis results, the minimum linewidth of the waveguide grating can reach 0.1 nm, the maximum SMSR can reach 13.2 dB, and the maximum reflectivity can reach 99%.